A randomized study comparing the effect of platelet-rich plasma and platelet-poor plasma for the treatment of plantar fasciitis (Research, Society and Development, 2023)
Objective: To verify the effectiveness of therapy with platelet-rich plasma (PRP) in patients with plantar fasciitis, this prospective, longitudinal, double-blind study was carried out. Methodology: Twenty-three participants with chronic plantar fasciitis aged > 20 years, already treated with conventional methods were included. Participants were randomly divided into platelet-poor plasma (PPP) and platelet-rich plasma (PRP) groups. Double centrifugation was carried out to prepare the platelets samples and two millilitres of PPP (supernatant fraction) or PRP (sediment fraction) were mixed with 1mL of 2% calcium gluconate solution and injected in the plantar fascia, as a single dose. A follow-up at 15 days and then every 60 days up to 180 days of application was carried out and a visual analogue scale (VAS) for pain assessment and the quality-of-life scale validated by the American Orthopedic Foot and Ankle Society (AOFAS) were used to measure the outcomes. Results: A reduction in pain (VAS 8 to 4), in both groups, was seen in the first 15 days and remained up to the 6th month after the application of plasmas, however, no difference was observed between the groups. No significant improvement was observed in the quality of life of the patients. Conclusion: PPP or PRP were able to reduce the VAS, but the presence of platelets did not have a role in the pain relief. Other factors in the plasma may play a role in reducing the pain caused by plantar fasciitis for a period of up to 180 days.